Social and Environmental Responsibility by Limited Liability Companies Regarding Corpoorate Social Responsibility (Csr) (Study: On PT. Mitra Karya Tri Utama (Sampoerna)) - Sekar Aini Sudjatmiarsih (UM Purwokerto Press, 2023)
Law No. 40/2007 on Limited Liability Companies requires companies to carry out activities known as Corporate Social Responsibility (CSR). Given this, companies have a role and responsibility in the implementation of CSR activities and as a form of concern for the community and the environment. PT Mitra Karya Tri Utama is a company engaged in cigarette rolling services that is obliged to carry out CSR activities. In running this program, the company needs to incur costs, from these costs the program can run well. Based on the above problems, the following problems can be formulated, First, how is the form of implementation of social and environmental responsibility by a limited liability company (PT). Second, how is the mechanism regarding the financing of social and environmental responsibility by a limited liability company (PT). The purpose of this study, First, can know and analyze how social and environmental responsibility. Second, can know and analyze the mechanism of financing social and environmental responsibility. The research method used is empirical juridical. From the results of research and discussion, it is concluded that First, PT Mitra Karya Tri Utama (Sampoerna) implements this CSR program by issuing a number of funds to be handed over to orphanages, residents around the company, and social services, but more often done for donations to orphanages. Second, the self-funding mechanism at PT Mitra Karya Tri Utama is an amount of Rp 5,000,000, from which CSR programs will be carried out within 1 month.